Vesicle trafficking in rice: too little is known - Zhu, Xiaobo; Yin, Junjie; Guo, Hongming; Wang, Yuping; Ma, Bingtian (Frontiers in Plant Science, 2023)
The vesicle trafficking apparatus is fundamental machinery to maintain the homeostasis of membrane-enclosed organelles in eukaryotic cells. Thus, it is broadly conserved in eukaryotes including plants. Intensive studies in the model organisms have produced a comprehensive picture of vesicle trafficking in yeast and human. However, with respect to the vesicle trafficking of plants including rice, our understanding on the components and their coordinated regulation is very limited. At present, several vesicle trafficking apparatus components and cargo proteins have been identified and characterized in rice, but there still remain large unknowns concerning the organization and function of rice vesicle trafficking system. In this review, we outline the main vesicle trafficking pathways of rice based on knowledge obtained in model organisms, and summarize current advances of rice vesicle trafficking. We also propose to develop methodologies applicable to rice and even other crops for further exploring the mysteries of vesicle trafficking in plants.